2018 International Symposium on Electromagnetic Compatibility (EMC EUROPE) 2018
DOI: 10.1109/emceurope.2018.8485050
|View full text |Cite
|
Sign up to set email alerts
|

Chasing the Wave in a Reverberation Chamber

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Accurate results were shown in the 1 to 6 GHz band for all three methods [12]. Considering the trend of harvesting all possible frequency bands, it is key to push this approach to a wider frequency range and verify it for more chamber types, such as chambers with a moving wall [17] or VIRCs [18]. In addition, measuring large-form-factor devices at high frequencies dictates the use of an electrically extremely large reverberation chamber.…”
Section: Introductionmentioning
confidence: 96%
“…Accurate results were shown in the 1 to 6 GHz band for all three methods [12]. Considering the trend of harvesting all possible frequency bands, it is key to push this approach to a wider frequency range and verify it for more chamber types, such as chambers with a moving wall [17] or VIRCs [18]. In addition, measuring large-form-factor devices at high frequencies dictates the use of an electrically extremely large reverberation chamber.…”
Section: Introductionmentioning
confidence: 96%
“…After, one averages over frequency samples to obtain the PDP. h(t, n) is the chamber's impulse response for the n th mode-stirring sample, determined by taking the average of the inverse Fourier transforms (IFT) of S 12 and S 21 , and is given by [15]. The chamber decay time is a measure of the time it takes for the power to be dissipated from the moment the energy source is turned off until the moment where the signal is too low to measure, neglecting the early time behavior.…”
Section: Theory a Chamber Decay Timementioning
confidence: 99%
“…Both stirrers were varied over 10 different positions each and every measurement used at least P = 6 antenna positions for a total of 600 mode-stirring samples. The second measurement location is the Eindhoven University of Technology (TUe) RC with a volume of 72.72 m 3 and an unfolding wall acting as a stirrer, changing its shape and boundary conditions for every position, while the chamber volume remains the same [15]. 100 different wall positions were used in these measurements, which have been proven by earlier unpublished studies to have low correlation.…”
Section: Experiments Design and Modelmentioning
confidence: 99%
“…The effect of an antenna placed close to an absorbing material is discussed in [30], where it is shown that the absorbing material prevents part of the radiation from interacting with the chamber walls and stirrer(s). In addition to the actual late-time [20], [31] loading of the chamber by the absorbers, thereby changing the chamber's Q or time constant, they prevent energy from coupling from one antenna into the other antenna during chamber build-up [30], an effect that is also known as the Proximity Effect [6]. From an antenna efficiency measurement viewpoint, the absorbing material acts as an additional antenna load and, thus, results in a different antenna efficiency and input impedance than its free-space behavior.…”
Section: Introductionmentioning
confidence: 99%